Thermal-mechanical Characteristic Analysis of Hydro-viscous Clutch for Friction Plate with Radial Groove - Cui Jiasen; Wang Yun; Chen Liyu; Chen Zhe; Yang Xiaming; Xie Fangwei (Jixie chuandong, 2018)
The heat convection of friction plate with oil film comprehensive is taken into account,the mixed friction process thermal structural coupling physical model of friction plate is established for simulation,the temperature field and stress field of friction plate with radial grooves during mixed friction process are simulated by using finite element method. The groove width and depth on the temperature field and stress filed of the friction plate are comparatively analyzed under the same conditions. The research results show that the temperature in the groove of the friction plate is much lower than that of the contact regions,and the center of the contact regions present a hot spot with higher temperature,the friction plate temperature decreases with the increase of the groove width,and first lower and then increased with the increase of the groove depth. The research results have engineering and theoretical guiding value for the prediction of the temperature field and stress field during the operation process of the hydro-viscous clutch and the design of the friction plate.